Vibrational Damping Behaviors Of Graphene Nanoplatelets Reinforced NR/EPDM Nanocomposites - Mohamad, Noraiham; Yaakub , Juliana; Ab Maulod, Hairul Effendy; Abd Razak, Jeefferie; Yaakob, Mohd Yuhazri; Lau, Kok Tee; Ahsan, Qumrul; Shueb, Mohammed Iqbal; Othman, R. (Universiti Malaysia Pahang, 2017)
Vibrational damping behaviors of graphene nanoplatelets (GNPs) reinforced natural rubber/ethylene-propylene-diene rubber (NR/EPDM) were investigated. The nanocomposites were prepared through melt compounding using a Haake internal mixer. In this study, GNPs reinforced NR/EPDM nanocomposites were characterized for damping properties towards the effect of GNPs loading (1, 3 and 5 wt%) and chitosan-functionalization. The results indicate the addition of GNPs have significantly improved both log decrement and damping ratio values correlated to the enhanced damping property of the nanocomposites. Chitosan-functionalized GNPs seem to slightly hamper the increase of damping properties contributed by incorporation of GNPs in NR/EPDM blends. These findings were further supported by thermal and morphological studies through dynamic mechanical analysis (DMA) and transmission electron microscopy (TEM) analysis. The storage modulus, loss modulus and tan δ showed good agreement with the vibrational damping test. Meanwhile, TEM analysis revealed the existence of intercalated and exfoliated structure of GNPs in NR/EPDM matrix which resulted in improved vibration damping properties of the nanocomposites for the potential used as vibration insulator.